Learning Model of Prose Appreciation Based on Inspirational Figure Story as an Effort to Build Students' Character - U'um Qomariyah (TRANSFORMATIKA, 2018)
This paper attempts to describe the prose appreciation model based on the inspirational experience of the character for Indonesian Language and Literature Education students. The development model is designed to improve student learning outcomes and as a follow-up to character formation. The needs of model development are obtained from questionnaires, observations, and interviews that include: (1) the need for teaching materials, (2) the needs of lecturers, and (3) the needs of the students. Characteristics of the model is based on the principles of model development obtained from the needs analysis. Referring to these two things can be obtained ten principles of learning model, including: (1) completeness principle, (2) cooperation, (3) effectiveness, (4) fun, (5) active learning, (6) modeling, 7) evaluative, (8) motivation, (9) variative, (10) mentoring, and (11) integrative. What model designs are based on the principles of development and the results of field studies and literature. Development of the model design consists of: (a) orientation stage (b) contemplation, (c) exploration stage, (d) imitation, and (e) generalization.